Advanced PHY/MAC Design for Infrastructure-less Wireless Networks - Furtado, António Eduardo Carreiro (2018)
Wireless networks play a key role in providing information exchange among distributed mobile devices. Nowadays, Infrastructure-Less Wireless Networks (ILWNs), which include ad hoc and sensor networks, are gaining increasing popularity as they do not need a fixed infrastructure. Simultaneously, multiple research initiatives have led to different findings at the physical (PHY) layer of the wireless communication systems, which can effectively be adopted in ILWNs. However, the distributed nature of ILWNs demand for different network control policies that should have into account the most recent findings to increase the network performance. This thesis investigates the adoption of Multi-Packet Reception (MPR) techniques at the PHY layer of distributed wireless networks, which is itself a challenging task due to the lack of a central coordinator and the spatial distribution of the nodes. The work starts with the derivation of an MPR system performance model that allows to determine optimal points of operation for different radio conditions. The model developed and validated in this thesis is then used to study the performance of ILWNs in high density of transmitters and when the spectrum can be sensed a priori (i.e. before each transmission). Based on the theoretical analysis developed in the thesis, we show that depending on the propagation conditions the spectrum sensing can reduce the network throughput to a level where its use should be avoided. At the final stage, we propose a crosslayered architecture that improves the capacity of an ILWN. Different Medium Access Control (MAC) schemes for ILWNs adopting MPR communications are proposed and their performance is theoretically characterized. We propose a cross-layer optimization methodology that considers the features of the MPR communication scheme together with the MAC performance. The proposed cross-layer optimization methodology improves the throughput of ILWNs, which is validated through theoretical analysis and multiple simulation results.